Base station location and terminal assignment problem in WiMAX networks - Hanoğlu, Vahit. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
Although the base station location and terminal assignment problem in cellular networks has been extensively studied, the previous work in the literature cannot be directly applied to wireless networks that support multiple classes of connections, such as WiMAX. This situation arises from the fact that WiMAX incorporates several service flows at each subscriber station for QoS provisioning. In this thesis, time slots are used to represent the requirements and the constraints as opposed to the classical representation that uses the bit rates. An optimization problem, which includes both the base station location and the terminal assignment problems, is defined and formulated. As the solution, two deterministic heuristic algorithms, DEAR (DEploy-Assign-dRop) and CLEAN (Cluster-dEploy-AssigN), are proposed, which follow elimination and divideand- conquer techniques, respectively. Integer linear programming (ILP) solutions show that formulating real life cases with the defined formulation and using heuristic algorithms are suitable and reasonable.
Keywords: Wireless communication systems.; Broadband communication systems.; IEEE 802.16 (Standard)